Iowa Birdline update, October 2, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa Birdline update for October 2, 1995. The highlights for the update include sightings of a Fish Crow, two Sabine's Gulls, Nelson's Sharp-tailed Sparrow, Sanderling, an immature Northern Goshawk and a Mourning Warbler. Epson - sheet feed/flatbed